2021
DOI: 10.1007/s00784-021-04030-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spray air settings of speed-increasing contra-angle handpieces on intrapulpal temperatures, drilling times, and coolant spray pattern

Abstract: Objectives Decreasing aerosol leaks are of great interest, especially in the recent era of COVID-19. The aim was to investigate intrapulpal heat development, coolant spray patterns, and the preparation efficiency of speed-increasing contra-angle handpieces with the spray air on (mist) or off (water jet) settings during restorative cavity preparations. Methods Standard-sized cavities were prepared in 80 extracted intact human molar teeth using diamond cylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, during cavity preparation for direct or indirect restorations, the enamel and DEJ are partially removed, and the dentin thickness is reduced according to the extent of the caries or depending on the special cavity design. Hard tissue removal during cavity preparation and several steps of the adhesive restorative procedure (i.e., polymerization of the adhesive layer and the RBC/adhesive luting agent, and the polishing procedure) may cause thermal damage due to the weakened thermal insulation effect, especially in younger patients with wider dentinal tubules [ 63 , 64 ]. The present study investigated four thicknesses (1.0 mm, 1.5 mm, 2.0 mm, and 2.5 mm) of the remaining dentin layer.…”
Section: Discussionmentioning
confidence: 99%
“…However, during cavity preparation for direct or indirect restorations, the enamel and DEJ are partially removed, and the dentin thickness is reduced according to the extent of the caries or depending on the special cavity design. Hard tissue removal during cavity preparation and several steps of the adhesive restorative procedure (i.e., polymerization of the adhesive layer and the RBC/adhesive luting agent, and the polishing procedure) may cause thermal damage due to the weakened thermal insulation effect, especially in younger patients with wider dentinal tubules [ 63 , 64 ]. The present study investigated four thicknesses (1.0 mm, 1.5 mm, 2.0 mm, and 2.5 mm) of the remaining dentin layer.…”
Section: Discussionmentioning
confidence: 99%
“…Although the new ‘no chip air’ function is innovative, whether the absence of air spray could affect the pulpal temperature of the drilled tooth remains unknown. More recently, Lempel and Szalma 38 found that effective ‘no chip air’–mediated reduction of aerosol is possible while maintaining a thermally safe environment for the tooth.…”
Section: Discussionmentioning
confidence: 99%
“…At a 15-mL min −1 water flow rate, concern has been expressed that a change of 5.5°C (the threshold to protect the pulp) can be exceeded with 1 mm remaining dentine thickness. Therefore, 30 mL min −1 was advised when using 200,000 rpm (Lempel and Szalma 2021). In that study, temperature was measured via a thermocouple, which also risks the peak temperature being missed compared to recording an area of interest as seen with the thermograph in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Modern HSCAHs use air and water to cool, lubricate, and clean the cutting bur, thus reducing energy transfer to the tooth. One recent study indicated that the use of an HSCAH with only water coolant can result in acceptable temperature increases (Lempel and Szalma 2021). This was reported as highly dependent on the water flow rate when the remaining dentine thickness was 1 mm.…”
Section: Introductionmentioning
confidence: 99%